Danshen (Salvia miltiorrhiza) Compounds Improve the Biochemical Indices of the Patients with Coronary Heart Disease. (5th June 2016) - Liu, Boyan; Du, Yanhui; Cong, Lixin; Jia, Xiaoying; Yang, Ge
Abstract : Danshen was able to reduce the risk of the patients with coronary heart disease (CHD), but the mechanism is still widely unknown. Biochemical indices (lipid profile, markers of renal and liver function, and homocysteine (Hcy)) are closely associated with CHD risk. We aimed to investigate whether the medicine reduces CHD risk by improving these biochemical indices. The patients received 10 Danshen pills (27 mg/pill) in Dashen group, while the control patients received placebo pills, three times daily. The duration of follow-up was three months. The serum biochemical indices were measured, including lipid profiles (LDL cholesterol (LDL-C), HDL-C, total cholesterol (TC), triglycerides (TG), apolipoprotein (Apo) A, ApoB, ApoE, and lipoprotein (a) (Lp(a))); markers of liver function (gamma-glutamyl transpeptidase (GGT), total bilirubin (TBil), indirect bilirubin (IBil), and direct bilirubin (DBil)); marker of renal function (uric acid (UA)) and Hcy. After three-month follow-up, Danshen treatment reduced the levels of TG, TC, LDL-C, Lp(a), GGT, DBil, UA, and Hcy (P < 0.05 ). In contrast, the treatment increased the levels of HDL-C, ApoA, ApoB, ApoE, TBil, and IBil (P < 0.05 ). Conclusion . Danshen can reduce the CHD risk by improving the biochemical indices of CHD patients.